2017
DOI: 10.1016/j.tranon.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization and Sensitivity to Human Adenovirus Serotypes 3, 5, and 11p of New Cell Lines Derived from Human Diffuse Grade II to IV Gliomas

Abstract: BACKGROUND: Oncolytic adenoviruses show promise in targeting gliomas because they do not replicate in normal brain cells. However, clinical responses occur only in a subset of patients. One explanation could be the heterogenic expression level of virus receptors. Another contributing factor could be variable activity of tumor antiviral defenses in different glioma subtypes. METHODS: We established a collection of primary low-passage cell lines from different glioma subtypes (3 glioblastomas, 3 oligoastrocytoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In support, Niittykoski et al observed that short-term glioma cell cultures significantly reduced or lost DSG2 but not CD46 expression during passaging compared with their parental tumor tissues. 19 Finally, we found that CD46 was expressed abundantly in all of the tested human cell cultures, consistent with previous reports. 19,20 Altogether, these data imply that for personalized oncolytic virotherapy, if applicable at all, measuring the expression levels of adenoviral receptors perioperatively should be preferable and more relevant from a practical point of view, although the expression levels of CAR, DSG2, and CD46 and integrins aVb3/aVb5 did not predict, at least in vitro, the relative oncolytic efficiency of the fiber-modified rAds tested in our study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In support, Niittykoski et al observed that short-term glioma cell cultures significantly reduced or lost DSG2 but not CD46 expression during passaging compared with their parental tumor tissues. 19 Finally, we found that CD46 was expressed abundantly in all of the tested human cell cultures, consistent with previous reports. 19,20 Altogether, these data imply that for personalized oncolytic virotherapy, if applicable at all, measuring the expression levels of adenoviral receptors perioperatively should be preferable and more relevant from a practical point of view, although the expression levels of CAR, DSG2, and CD46 and integrins aVb3/aVb5 did not predict, at least in vitro, the relative oncolytic efficiency of the fiber-modified rAds tested in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of CAR in glioma tissues and short-term primary glioma cultures was frequently barely detectable. [19][20][21][22]25 However, in established glioma cell lines and in mouse xenografts of shortterm glioma cultures, CAR expression was found to be upregulated compared with that of their parental tumors. 21 A similar and seemingly contradictory situation with the expression of CAR was also reported for melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several research groups recently reported Ad11-based vectors, RCAd11p vector constructs have marked differences. In general, Ad11 exhibits enticing potential as a virotherapy agent [30]. Accordingly, a variant of Ad11 (ColoAd1) was recently investigated in phase I clinical trials for the treatment of solid tumours [31].…”
Section: Discussionmentioning
confidence: 99%